Water management in the next century - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
-correction- An announcement and call for papers was made in Spore 34 page 12 for the 15th Congress of the International Commission on Irrigation and Drainage (ICID) to be held in The Hague, The Netherlands, 6-11 September 1993. The final paragraph...